Analisis Fundamental Terhadap Return Saham Syariah Pada Jakarta Islamic Index Tahun 2017-2021 - Viyanti, Amalia; Hanif, Aisha (Indonesian Journal Publisher, 2020)
The goal of an investor investing in stocks is to get a return. In predicting returns, an investor must look at the company's performance which can be done by fundamental analysis. The purpose of this study was to determine the effect of firm size, DER, EPS, and PBV on Islamic stock returns in the Jakarta Islamic Index (JII) in 2017-2021. The analytical method used is multiple linear regression analysis. The results of hypothesis testing prove that only DER has effect on Islamic stock returns. Firm size, EPS, and PBV has no effect on Islamic stock returns. The results of this study provide guidelines for making decisions about investing in stocks related to Islamic stock returns and can be used as a reference for those who wish to conduct further research on Islamic stock returns or similar research in the future.